Fracture nonunion in long bones: A literature review of risk factors and surgical management. (June 2021) - Nicholson, JA; Makaram, N; Simpson, AHRW; Keating, JF
Highlights: The burden of a long bone nonunion is substantial with pain, loss of function and psychological distress commonly encountered. Nonunion in clinical practice is most commonly associated with long bone fractures of the forearm, humerus, tibia, clavicle and femur. The majority of nonunions can be effectively managed with conventional surgical techniques. Abstract: Nonunion following a long bone fracture causes considerable morbidity when it occurs. Risk factors depend on specific fractures but there is a complex interplay of injury severity, comorbidities, patient medication and infection. The majority of nonunions occur after long bone fractures with the tibia, femur, forearm, humerus and clavicle predominating. Despite interest in the biological augmentation of fracture healing, the majority of nonunions can be effectively managed with conventional surgical techniques. In this review we present a review of risk factors for nonunion and the outcome following surgical management.